Self-Efficacy and Quality of Life Among Coronary Heart Disease Patients: A Cross-Sectional Study - Yosi Oktarina; Nurhusna Nurhusna; Tuti Aryani (Universitas Ahmad Dahlan, 2023)
Coronary heart disease had an impact on functional status and quality of life. Self-Efficacy was needed in self-care management in coronary heart disease patients. The main obective of this study was to identify the relationship between self-efficacy and quality of life in coronary heart disease patients. This study was conducted using a cross-sectional design and the samples were 100 patients with coronary heart disease recruited through consecutive sampling from Regional General Hospital Cardiology, Jambi Province The instruments used included The self-efficacy for managing chronic diseases 6-item scale (SEMCD-6) and The World Health Organization Quality of Life Brief Version (WHOQOL-Bref), while the data analysis was performed using Spearman correlation. The results showed there was a positive correlation between self-efficacy and the four domains of quality of life (physical, psychological, social relations, and environmental domains ( p-value < 0.05). It was hoped that nurses could increase patient self-efficacy by providing motivation and education for both patients and family to improve the patient's quality of life.Keywords: Self-Efficacy; Quality of Life; Coronary Heart Disease